Authors of Lithuanian books in the first part of 19th century - Aušra Navickienė (Knygotyra)
During 1795-1864, there were 131 authors of Lithuanian books in Greater Lithuania (they are the main object of our examination). The books of 13 earlier writers were also published, and the literary production of 49 foreign authors was translated into Lithuanian. (The concept "author" in this article is used in a broad sense and includes not only the concrete authors of the books but also compilers, editors, translators, and makers. The concept "book" includes manuscripts and printed works of that time.)